A marca da passagem de Córdelia: um memorial descritivo do espetáculo “Cordélia Brasil” - ARAÚJO, Juliana Maria Ayres (2022)
This work will record the creative process of the play “Cordelia Brasil” in 2019 by the “Casa de Shakespeare” Theater Group that acts in Belém do Pará. It seeks to describe the steps of the production of a play by an independent group that has no sponsorship. The data collected were from a process lasting eight months, where the beginning was characterized by the planning and execution of rehearsals, while the end was reserved for the production of costumes, set design, lighting, propagation and presentation. It was during this process that the proposal came up to create a descriptive memorial that conveys the obstacles of undertaking a low-budget theatrical project.